Study of Conventional and Novel Risk Factors of Ischemic Stroke in Eastern India - Biswas, Nirendra Mohan; Ghosh, Dipendra Nath; Sengupta, Amitabha; Sen, Sumit; Jash, Debraj; Saha, Kaushik; Banerjee, Arpita; Mandal, Pranab (Journal of Medicine, 2013)
Background: Stroke accounts as one of the leading cause of morbidity and mortality and third most common cause of death worldwide. In a significant percentage of stroke patients no definite cause can be identified. These group of unknown cause, the so-called cryptogenic strokes are associated with some novel risk factors and now a major focus for clinical discussion. Objectives: To find out conventional risk factors behind ischemic stroke and to establish correlation between ischemic stroke with elevated lipoprotein(a), Homocysteinemia, elevated High-sensitivity C-reactive protein (hs CRP),Systemic Lupus Erythematous (SLE) and chronic H.pylori infection and carotid intimo-medial thickness(CIMT). Materials and methods: Thirty (30) admitted ischemic stroke patients based on WHO definition and confirmed by axial CT and or MRI Scan. were included. Thirty (30) controls were recruited from close relatives of the patients attending the Medicine OPD without any prior history of stroke or coronary heart diseases. Risk factors were documented on the basis of biochemical tests performed. Results : Statistically significant association of ischaemic stroke with diabetes,hypertension, smoking, homocysteine, Lp(a), hsCRP, LVH, CIMT,H.pylori infection. No association of valvular heart disease, atrial fibrillation, A.N.A was found with ischaemic stroke. Conclusion: In addition to measures that include blood sugar, blood pressure and lipid control routine estimation of Lp(a), homocysteine level, monitoring of atherosclerotic changes in carotid artery by Doppler study, echocardiographic monitoring of LVH should be done so that appropriate steps can be taken to avert an attack of stroke. Lastly early detection and eradication of H.pylori is always advisable to reduce the incidence of ischemic stroke. DOI: http://dx.doi.org/10.3329/jom.v14i1.13165 J MEDICINE 2013; 14 : 11-17